Proceso atención de enfermería en gestante adolescente de 15 semanas más infección del tracto urinario. - Jurado Cortez, Alexander Maximiliano (2021)
The present clinical case focuses on the state of a pregnant patient of 15 weeks and 17 years of age, with a urinary tract infection, a history of infections prior to the consultation, she is taken by her partner to the emergency area for presenting suprapubic pain, dysuria and frequency, with 11 days of evolution. Through laboratory tests, the diagnosis of urinary tract infection is determined. Urinary tract infections are frequent during pregnancy, they can be asymptomatic or symptoms such as dysuria, frequency, hematuria, pyuria and suprapubic pain may be perceived. Most of the undiagnosed asymptomatic bacteriurias will evolve to a clinical picture of cystitis and in the worst case pyelonephritis. The main cause for the appearance of urinary tract infections in pregnant women includes physiological and hormonal changes, the absence of optimal prenatal control and avoiding preventive actions. The nursing professional makes intervention necessary through the nursing care process, to identify real and potential risks, prioritize patient care and satisfaction, to solve health problems. The main objective of this clinical case is to identify the appropriate nursing care process, which concludes in a correct evaluation of the patient and the improvement in her condition.